1995
DOI: 10.1007/bf00202646
|View full text |Cite
|
Sign up to set email alerts
|

Deletion analysis of the Brassica napus cruciferin gene cru 1 promoter in transformed tobacco: promoter activity during early and late stages of embryogenesis is influenced by cis-acting elements in partially separate regions

Abstract: To define sequences in the cruciferin gene cru1 promoter of importance for expression, tobacco (Nicotina tabacum L.) plants were transformed with constructs in which the cru1 promoter, in front of the intact cru1 structural gene, was truncated at -1216, -974, -736, -515, -306, -46 and -17 bp relative to the cap-site. Cru1 expression in tobacco seeds was studied by Northern analysis, Western analysis and in-situ hybridizations. Comparisons of the Northern analysis of RNA from tobacco seeds harvested at 18 d aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…In this region, SEF3 and SEF4 motifs are good candidates because these motifs are important binding sites for transcription factors that enhance gene expression of several storage proteins in soybean seed (for example, b-conglycinin, Lessard et al 1991;or 7S globulin, Hayashi et al 1997). These motifs, observed in various species such as in the promoter of the cruciferin CRU1 gene of Brassica napus (Sjödahl et al 1995), were also observed in the promoter region of the chalcone synthase genes CHS7 and CHS8 which are expressed in the seed coat in soybean (Yi et al 2010). …”
Section: Luplr1 In Silico and Functional Analysesmentioning
confidence: 87%
“…In this region, SEF3 and SEF4 motifs are good candidates because these motifs are important binding sites for transcription factors that enhance gene expression of several storage proteins in soybean seed (for example, b-conglycinin, Lessard et al 1991;or 7S globulin, Hayashi et al 1997). These motifs, observed in various species such as in the promoter of the cruciferin CRU1 gene of Brassica napus (Sjödahl et al 1995), were also observed in the promoter region of the chalcone synthase genes CHS7 and CHS8 which are expressed in the seed coat in soybean (Yi et al 2010). …”
Section: Luplr1 In Silico and Functional Analysesmentioning
confidence: 87%
“…Conserved motifs exist in the promoter regions of seed storage protein genes across diverse plant species [157] suggesting that the regulation of seed storage protein biosynthesis is governed by transcriptional mechanisms that evolved early in the evolution of the plant kingdom. The disruption of some of these conserved motifs in the canola cruciferin-encoding cru1 gene [158] and the napin-encoding napA gene [159] led to reduced accumulation of the respective protein product. Multiple transcription factors are known to regulate the expression of seed storage protein genes in Arabidopsis: ABSCISIC ACID INSENSITIVE 3 (ABI3) [160][161][162][163], FUSCA 3 (FUS3) [161,164], LEAFY COTYLEDON 1 (LEC1) [164][165][166], LEC2 [161], and multiple MYC transcription factors [167].…”
Section: Genetic Control Of Seed Storage Proteins In Canolamentioning
confidence: 99%
“…Conserved motifs exist in the promoter regions of seed storage protein genes across diverse plant species [ 157 ] suggesting that the regulation of seed storage protein biosynthesis is governed by transcriptional mechanisms that evolved early in the evolution of the plant kingdom. The disruption of some of these conserved motifs in the canola cruciferin-encoding cru1 gene [ 158 ] and the napin-encoding napA gene [ 159 ] led to reduced accumulation of the respective protein product. Multiple transcription factors are known to regulate the expression of seed storage protein genes in Arabidopsis : ABSCISIC ACID INSENSITIVE 3 ( ABI3 ) [ 160 , 161 , 162 , 163 ], FUSCA 3 ( FUS3 ) [ 161 , 164 ], LEAFY COTYLEDON 1 ( LEC1) [ 164 , 165 , 166 ], LEC2 [ 161 ], and multiple MYC transcription factors [ 167 ].…”
Section: Genetic Control Of Seed Storage Proteins In Canolamentioning
confidence: 99%